The Effect of Locus of Control on Learning Achievement during the Covid-19 Pandemic - Nasir Nasir; Sriyanti Mustafa; Sulvianti Sulvianti; Nur Azizah (Universitas Jambi, Indonesia, 2021)
Learning during the Covid-19 pandemic is a challenge for students and has an impact on learning achievement. This study aimed to determine the effect of locus of control on learning achievement during the covid-19 pandemic. This research was conducted at one state junior high school, Soppeng Riaja, South Sulawesi by using a quantitative approach. Data were obtained by using a questionnaire and documents of learning achievement data in the form of report cards. The collected data were then analyzed using descriptive statistics and inferential statistics. Descriptive statistical data analysis showed that the average score of student learning achievement was in the moderate achievement category, meaning that during the COVID-19 pandemic, students’ learning abilities did not significantly decrease in achievement. Therefore, it was considered that students could still learn properly even though it was done online. Furthermore, the results of the analysis of the inferential data indicated that the locus of control had a positive effect on the learning achievement of students. Thus, it can be concluded that the locus of control of students while studying during the Covid-19 pandemic was quite good and had a positive influence on the progress of learning achievement.